Detection of Giardia lamblia Cysts in Surface Waters of Rasht City, Iran - Elham saeedi; Nematollah Jonaidi Jafari; Ali Salehzadeh (Pasteur Institute of Iran, 2018)
Introduction: Giardia lamblia is a protozoan parasite with universal distribution in human populations. This infections transfer to human via contaminated foods and waters with Giardia cysts. The Knowledge on the incidence of this agent in the potential infection sources can provide valuable information for control and the spread of this parasite to human communities. This study was aimed to isolate and identify the Giardia lamblia cysts in the surface waters of Rasht city, Guilan province, north of Iran with microscopy and PCR assay. Methods: This cross-sectional study was performed on 45 samples of surface waters collected from rivers and wetlands in the vicinity of Rasht city. The samples were concentrated using nitrocellulose membrane filters, and the sediments were examined for Giardia cysts by microscopy with a magnification of 1000 X. Also, DNA was extracted from the sediments, and the heat shock protein gene of G. lamblia was amplified. Results: From 45 samples, 33.33% and 40% were positive by microscopy and PCR, respectively. Conclusion: In comparison with the standard microscopic method, PCR showed more sensitivity for detection of G. lamblia cysts in water samples.